Praseodymium-cerium oxide-infiltrated perovskite cathode with superior electrochemical performance for solid oxide fuel cells - Li, Hao-Yang (2025)
This study presents a high-performance solid oxide fuel cell employing a perovskite cathode, strontium iron molybdenum oxide [Sr2Fe1.5Mo0.5O6-δ (SFM)], infiltrated with praseodymium-cerium oxide [Pr0.2Ce0.8O2-δ (PCO)], a fluorite. This infiltration notably enhances the oxygen reduction reaction kinetics and long-term stability. Evidence of enhanced stability is seen through minimized impedance degradation over 50 h. Furthermore, PCO infiltration improves the cathode's resistance to chromium poisoning by suppressing strontium degradation. Compared to the bare SFM cathode, the PCO-infiltrated SFM composite cathode doubles the cell's power density at 800 °C.